Teachers’ Beliefs of Monolingualism in an International School - Ariyati, Dwi (ppjbsip, 2025)
This research explores the beliefs of Indonesian EAL teachers about monolingualism, they saw it as a challenge or a benefit and how they perceived students’ native language conducted in one of the International Schools in Jakarta, Indonesia. The participants of this research were three Indonesian EAL teachers who worked in an International School in Jakarta. This researched employed qualitative research, and semi-structured interviews to collect the data. For data analysis, this researched utilised thematic analysis to analyse and examine the similarity and differences from research participants response. The findings stated that Indonesian EAL teachers recognised monolingualism as a disadvantage. Furthermore, using one language in the classroom, it raised the challenges included students at the beginner level was struggling to communicate and exchange their minds if they did not know how to express themselves in English and the needed to balance content and language for the teachers. Due to these challenges, the strategies in classroom included small groups with mixed abilities of students’ English level and with one country. In addition, Indonesian EAL teachers perceived students' native language as a resource that should be taught at school, and it was helpful in expressing their thoughts and understanding the material. Abstrak Penelitian ini mengeksplorasi keyakinan guru EAL Indonesia tentang monolingualisme, bagaimana mereka memandangnya sebagai tantangan atau manfaat, dan bagaimana mereka memandang bahasa ibu siswa yang dilakukan di salah satu Sekolah Internasional di Jakarta, Indonesia. Partisipan penelitian ini adalah tiga guru EAL Indonesia yang bekerja di Sekolah Internasional di Jakarta. Penelitian ini menggunakan penelitian kualitatif dan wawancara semi-terstruktur untuk mengumpulkan data. Untuk analisis data, peneliti menggunakan analisis tematik untuk menganalisis dan memeriksa persamaan dan perbedaan dari tanggapan partisipan penelitian. Temuan penelitian menyatakan bahwa guru EAL Indonesia mengakui monolingualisme sebagai kerugian. Lebih lanjut, penggunaan satu bahasa di kelas menimbulkan tantangan, termasuk siswa tingkat pemula yang kesulitan berkomunikasi dan bertukar pikiran jika mereka tidak tahu cara mengekspresikan diri dalam bahasa Inggris, serta kebutuhan untuk menyeimbangkan konten dan bahasa bagi guru. Karena tantangan ini, strategi di kelas mencakup kelompok-kelompok kecil dengan kemampuan bahasa Inggris siswa yang beragam dan dengan satu negara. Selain itu, guru EAL Indonesia memandang bahasa ibu siswa sebagai sumber daya yang harus diajarkan di sekolah, dan hal itu membantu dalam mengekspresikan pikiran mereka dan memahami materi..